1998
DOI: 10.1128/iai.66.5.2349-2351.1998
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Gamma Interferon onChlamydia trachomatisGrowth in Polarized and Nonpolarized Human Epithelial Cells in Culture

Abstract: The effects of gamma interferon (IFN-γ) on Chlamydia trachomatis growth in polarized epithelial cells were examined. The range of IFN-γ concentrations causing aberrant chlamydial growth was wider in polarized than in nonpolarized cultures. Results indicate that chlamydial growth modulation in polarized cells readily leads to persistence and better reflects in vivo conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…These in vitro polarized culture systems resemble the environment encountered by pathogens in vivo more closely than do traditional cultures and thus may be a more appropriate way to assess host-pathogen interactions. We recently demonstrated that IFN-␥-mediated chlamydial persistence occurs in a polarized human epithelial culture system (18). The characteristics of persistent chlamydiae in polarized cells are the same as those described previously for nonpolarized cells, with one intriguing difference: substantially larger quantities of IFN-␥ are required to induce persistence or growth inhibition in the polarized cells.…”
supporting
confidence: 60%
See 3 more Smart Citations
“…These in vitro polarized culture systems resemble the environment encountered by pathogens in vivo more closely than do traditional cultures and thus may be a more appropriate way to assess host-pathogen interactions. We recently demonstrated that IFN-␥-mediated chlamydial persistence occurs in a polarized human epithelial culture system (18). The characteristics of persistent chlamydiae in polarized cells are the same as those described previously for nonpolarized cells, with one intriguing difference: substantially larger quantities of IFN-␥ are required to induce persistence or growth inhibition in the polarized cells.…”
supporting
confidence: 60%
“…Many distinctions between cells grown in a polarized or nonpolarized manner have been documented. These differences also have been noted to affect the way in which chlamydiae interact with their host cells; Wyrick et al have demonstrated an accelerated developmental cycle in polarized cells (34), and previously we have shown a difference in IFN-␥-mediated growth restriction based on host cell polarization status (18).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…For example, IFN‐γ induction of chlamydial persistence has been shown to occur in several host cell types, including HeLa cells (Hogan et al ., 2003). However, developing chlamydiae within HEC‐1B cells are resistant to IFN‐γ because these host cells do not produce indoleamine 2,3‐dioxgenase (IDO) in response to IFN‐γ (Kane and Byrne, 1998; Wyrick and Knight, 2004). To be certain that induction of chlamydial persistence during HSV‐2 co‐infection is not a specific property of HeLa cells, HEC‐1B cells were also utilized as host cells for co‐infection.…”
Section: Resultsmentioning
confidence: 99%